Patellofemoral pain in cyclists - Van Zyl, Elizabeth (MRC/UCT RU for Exercise and Sport Medicine, 2017)
The aim of this thesis was first to review the current literature that deals with patellofemoral pain in cyclists. The second aim was to investigate the possibility of reducing media-lateral deviation during the down stroke of cycling, by altering the biomechanics of the lower limb and, to observe the effect of this reduction on patellofemoral pain in a clinical trail. This thesis is in the format of two papers that is submitted for publication in sports medicine journals. The first paper is a review of the aetiology, biomechanics, diagnosis and management of patellofemoral pain in cyclists. The second is a research paper, titled: correcting lower limb biomechanics decreases patellofemoral pain (PFP) in cyclists.